Analisis Perbedaan Manajemen Koperasi Pegawai Republik Indonesia (KPRI) Berbadan Hukum (Studi Komparatif SMA Negeri 2 Padang dan SMA Negeri 7 Padang) - Reyhan Plangka Jamcia; Agus Irianto (Jurnal Salingka Nagari, 2023)
The purpose of this study was to determine the differences in planning, organization, actuating, and controlling cooperative employees of the Republic of Indonesia as legal entities (comparative study of Senior High School two of Padang and Senior High School seven of Padang). This type of research is a type of comparative research that uses primary data as research. Obtained from a questionnaire filled out by the cooperative members of Senior High School two of Padang and Senior High School seven of Padang. Sampling was done by using proportional random sampling. The analysis technique used is descriptive analysis and inductive analysis. This study shows that there are not the same Cooperative Employees of the Republic of Indonesia as a legal entity. In the planning and control variables, there are differences in management, while in the organizing and mobilizing variables, the Cooperative Employees of the Republic of Indonesia are the same as legal entities.